ENERGY STUDY OF A HEAT PUMP USED FOR AIR ( HEATING AND DEHUMIDIFICATION - Maia, N. L.; Diniz, M. L.; Gurgel, J. M. A. M.; Gondim, R. R.; Carvalho, M.; Luiz, M. R. (Revista de Engenharia Térmica, 2015)
Heat pump assisted dryers can realize considerable savings of primary energy as compared with conventionally-heated air drying. This manuscript analyzes the design and construction aspects of a heat pump assisted dryer for biological products. The performance of the heat pump is investigated through an energy analysis, carried out under operating conditions of practical interest. The system is operated using R22 and is also evaluated with respect to the coefficient of performance (COP). Although the current trend is to invest in low-energy, low-carbon technologies, heat pump assisted dryers remain underexplored in the industrial sector due to its more complex operation.